A Systematic Literature Review: Findings of Misconceptions in Atomic Structure Chemistry - Damayanti, Yosephine Debbie; Wulanningtyas, Melania Eva (Universitas Negeri Semarang, 2025)
This research aims to provide a comprehensive overview of the current state of research on atomic structure misconceptions, as well as identifying the best strategies to overcome them. Systematic Literature Review (SLR) approach to identify, study, evaluate, and interpret research results related to misconceptions in atomic structure material at the high school level. This approach was chosen because it is able to provide a systematic and comprehensive overview of various relevant research, so that it can find patterns, trends and research gaps that exist over a certain period of time. The analysis focuses on the forms of misconceptions, causal factors, and learning strategies to overcome these misconceptions which are based on the results of literacy studies, especially those originating from 10 selected articles (which were selected based on SLR-based research methods). The research results show that there are misconceptions in the concept of atomic structure starting from the concept of the atomic model, the quantum mechanical model, the Aufbau principle, the Hund principle, the Pauli exclusion principle, to the sub-atomic concept of the composition of an atom. The results of this study provide important insight for teachers and curriculum developers regarding steps that can be taken to reduce misconceptions.